MANHAJ ULAMA DALAM MENJAGA OTENTISITAS HADIS MELALUI METODE AL-TAKHRĪJ DAN AL-RIJĀL - Luaily, Anjaliyatul; Mawaddah, Mawaddah; Masruroh, Masruroh; Muyessaroh, Muyessaroh; rahman, Fathurrahman (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Hadith is one of the main foundations in Islam that contains the traditions and teachings of Prophet Muhammad SAW as an explanation of the Qur’an. The role of hadith is very important, especially in establishing laws that are not explained in detail in the Qur’an, such as procedures for prayer and zakat. To maintain its authenticity, the companions and scholars have conducted rigorous verification from the beginning through scientific study in the discipline of hadith. The peak development of this science occurred in the 4th century Hijri, marked by the emergence of hadith works that not only focused on collection but also on verification, criticism, and more systematic explanation. The hadith books during this period had more complex academic characteristics, including classification of hadith based on the level of authenticity, the origin of narration, and the inclusion of sharh or commentary. In the hadith scholarly tradition, there are two types of books that play an important role, namely Kutub al-Takhrīj and Kutub al-Rijāl. This study uses a library research method by analyzing primary and secondary sources related to the theme. The study concludes that in the hadith scholarly tradition, two types of books hold an important role, namely Kutub al-Takhrīj and Kutub al-Rijāl. Both complement each other in the hadith research process because the validity of the sanad and matan can only be determined through a combination of narrative analysis and the credibility of the narrators. Keywords: Manhaj, Kutub al-Takhrīj, Kutub al-Rijāl.